Mapping associations: exploring divergent thinking through mind mapping. Issue 1 (3rd April 2019) - Leeds, Alex Julian; Kudrowitz, Barry; Kwon, Jieun
Abstract: This study is a preliminary inquiry into the structure of mental associations as captured by the Mind Mapping process. Participants generated mind maps around a common central theme. The average frequency occurrence of items mentioned in the maps (i.e., responses) was used as a measure of the response's relative 'uniqueness.' Although the creation of these mind maps was not framed as a Divergent Thinking task, interesting parallels to other Divergent Thinking tasks are reported and compared. This study expands upon the Serial Order Effect by utilizing the tree-graph structure of mind maps to parse out how the depth, breadth, and order of associations relates to uniqueness. The data shows a moderate relationship between order and uniqueness, and a strong relationship between depth and uniqueness. However, higher quantity of deeper responses does not indicate higher average uniqueness of responses. The results suggest that the latent dimensions of depth and breadth are not represented by 'order' and are absent in list formats. These results may inform more accurate Divergent Thinking assessments and better tools for aiding an idea generation processes.